How access to irrigation influences poverty and livelihoods: a case study from Sri Lanka. Impact assessment of infrastructure projects on poverty reduction - Senaratna Sellamuttu, Sonali; Aida, T.; Kasahara, R.; Sawada, Y.; Wijerathna, D. (Japan International Cooperation Agency, 2013)
This study combines a livelihoods approach with a regression approach to quantify the effectiveness of irrigation infrastructure investment on improving people's livelihood strategies. Using a unique data set based on households in southern Sri Lanka, and a natural experimental setting, we estimate from a two stage income regression model to show that irrigation access has a positive effect on income through livelihood choices. We also show through qualitative approaches that factors not linked to irrigation infrastructure may contribute to changes in livelihood portfolios. In addition, we highlight factors that result in certain households being unable to move out of poverty despite access to the improved irrigation infrastructure.